2008
DOI: 10.1097/pai.0b013e318047df6d
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD44s, CD44v6, and Hyaluronan Across the Spectrum of Normal-hyperplasia-carcinoma in Breast

Abstract: This study demonstrates decreased expression of CD44s accompanied by increased expression of CD44v6 and increased stromal HA in breast cancer. These findings suggest that CD44s, CD44v6, and HA play complementary roles in the development and progression of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
(38 reference statements)
0
28
1
Order By: Relevance
“…All isoforms of the protein are encoded by a single gene but are derived by alternative splicing (v1-v10) and variation in Oand N-glycosylations (47,48). CD44s, the smallest and most widely expressed isoform, is expressed in ductal epithelial cells and myoepithelial cells in all cases of normal and benign breast tissue; however, the expression of CD44s progres-sively decreases with increasing deviation from normal histology corresponding to our data (49). The peptides identified by our study were identical to protein sequences in both the N-terminal part (exon 2) and the C-terminal part of CD44, sequences present in all CD44 isoforms.…”
Section: Discussioncontrasting
confidence: 52%
“…All isoforms of the protein are encoded by a single gene but are derived by alternative splicing (v1-v10) and variation in Oand N-glycosylations (47,48). CD44s, the smallest and most widely expressed isoform, is expressed in ductal epithelial cells and myoepithelial cells in all cases of normal and benign breast tissue; however, the expression of CD44s progres-sively decreases with increasing deviation from normal histology corresponding to our data (49). The peptides identified by our study were identical to protein sequences in both the N-terminal part (exon 2) and the C-terminal part of CD44, sequences present in all CD44 isoforms.…”
Section: Discussioncontrasting
confidence: 52%
“…Although overexpression of CD44v6 has been reported in intestinal metaplasia of gastric mucosa, 45 to the best of our knowledge, this is the first time that overexpression of CD44v6 is described in hyperplastic lesions of the stomach. In other epithelial tissues such as the lung, 46 endometrium 47,48 and breast, 49 expression of CD44v6 in hyperplasia has already been observed. It remains to be clarified whether the overexpression of CD44v6 in hyperplastic/hyperproliferative lesions of gastric mucosa may indicate early premalignant changes not only in the abovementioned organs but also in the stomach.…”
Section: Cd44v6 In Gastric Cancermentioning
confidence: 99%
“…Also, HA was exclusively confined to the stroma in all cases of breast cancer and was not detected in epithelial cells. [16] However, in our study, HA was expressed in a tumor and stroma. Consistent with our finding, the expression of HA is correlated with malignancy in many cancers such as breast, lung and ovarian cancer.…”
Section: Discussionmentioning
confidence: 41%
“…Contradictory to our finding, Afify et al found HA tends to be expressed at the periphery of invasive tumor islands than the center, these findings supporting the argument that tumors release many soluble factors that increase HA. [16,66] In the present study, hyaluronan intensity of expression in tumor islands and stroma revealed significant differences among the studied different histological grades and types (p < .05). A Higher number of the examined SCC variant cases revealed strong HA expression in comparison with conventional SCC type.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation